Linguacultural Study Of Proverbs with A Monetary Component in English and Uzbek (Progress Annals: Journal of Progressive Research, 2025)
This study explores the linguacultural aspects of proverbs with a monetary component in English and Uzbek, highlighting their similarities and differences. Proverbs serve as linguistic and cultural artifacts that encapsulate a nation’s values, beliefs, and economic perspectives. In this research researcher used comparative linguistic and cultural analysis demonstrating how the economic worldview of English speakers aligns with individualism and financial rationality. Uzbek culture places more emphasis on morality and social responsibility in financial matters. The findings support the Sapir-Whorf hypothesis, affirming that language and cultural perspectives on wealth are deeply interconnected. This study contributes to the broader understanding of cross-cultural financial literacy and linguistic anthropology